2016
DOI: 10.1080/15592324.2016.1231293
|View full text |Cite
|
Sign up to set email alerts
|

NatA is required for suspensor development in Arabidopsis

Abstract: Suspensor development is essential for early embryogenesis. The filamentous suspensor plays vital roles in supporting the embryo proper and in exchanging nutrients and information between the embryo proper and embryo sac. In addition, at the globular stage, the uppermost suspensor cell differentiates into the hypophysis, which generates the progenitors of the quiescent center and columella stem cells. In naa10 and naa15 mutant plants, suspensor cell identity was found to be abnormal and embryo development was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In A. thaliana, NAA10 and NAA15 are classified as embryo defective genes [61]. Indeed, characterization of A. thaliana T-DNA insertion mutant NAA10 and NAA15 lines confirmed that loss of both subunits arrested embryos at the dermatogen to early globular stage and that AtNatA is required for the asymmetric division of the hypophysis, root meristem formation, and proper suspensor development [13,62,63]. Additionally, artificial miRNA (ami) AtNAA10 and AtNAA15 lines displayed severe developmental defects and growth retardation compared to wild-type A.…”
Section: Physiological Relevance Of Nats In Phototrophic Organismsmentioning
confidence: 98%
“…In A. thaliana, NAA10 and NAA15 are classified as embryo defective genes [61]. Indeed, characterization of A. thaliana T-DNA insertion mutant NAA10 and NAA15 lines confirmed that loss of both subunits arrested embryos at the dermatogen to early globular stage and that AtNatA is required for the asymmetric division of the hypophysis, root meristem formation, and proper suspensor development [13,62,63]. Additionally, artificial miRNA (ami) AtNAA10 and AtNAA15 lines displayed severe developmental defects and growth retardation compared to wild-type A.…”
Section: Physiological Relevance Of Nats In Phototrophic Organismsmentioning
confidence: 98%
“…This enzymatic process is catalyzed by a group of N-terminal acetyltransferases (NATs) and plays a pivotal role in various cellular processes, including protein stability, protein-protein interactions, and cellular localization (Aksnes et al, 2015; Bienvenut et al, 2012; Dikiy & Eliezer, 2014). There are seven known NAT types, with NatA being the most prominent, believed to be responsible for modifying 40-50% of the human proteome(Deng et al, 2019; Feng & Ma, 2016; Van Damme, 2021). The NatA complex is composed of the catalytic sub-unit NAA10, and the auxiliary sub-units NAA15 and HYPK (Deng et al, 2019; Dörfel et al, 2017; Feng et al, 2016; Knorr et al, 2019; Weidenhausen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%